Application of cooperative learning model in increasing students' motivation in doing physical fitness activities - Dinali, Lipran; Gunawan, Gunawan; Mursalim, Mursalim (Universitas Tanjungpura, 2024)
Cooperative learning models are known to be effective in increasing student engagement and motivation, especially in physical fitness activities. This study aimed to investigate the application of cooperative learning models to increase students' motivation to participate in physical fitness activities at SMANOR Tadulako. This study used a mixed methods approach, combining quantitative and qualitative data from surveys and observations. A total of 100 students were involved in the study, who were divided into groups for the cooperative learning intervention during physical education sessions. The results showed a significant increase in motivation levels, where students demonstrated higher participation, teamwork, and enthusiasm in physical fitness activities. The findings highlight the role of cooperative models in creating a supportive and engaging learning environment that encourages active participation and better learning outcomes.